Efficacy of Long-Term Indomethacin Therapy in Prolonging Pregnancy After Fetoscopic Laser Surgery for Twin-to-Twin Transfusion Syndrome: A Collaborative Cohort Study. Issue 9 (September 2022) - Mustafa, H. J.; Krispin, E.; Tadbiri, H.; Espinoza, J.; Shamshirsaz, A. A.; Nassr, A. A.; Donepudi, R.; Belfort, M. A.; Cortes, M. S.; Pederson, N.; Harman, C.; Turan, O. M.
Abstract : (Abstracted from BJOG 2022;129:597–606) Approximately 10% to 15% of monochorionic diamniotic twin pregnancies are affected by twin-to-twin transfusion syndrome (TTTS). Fetoscopic laser surgery is recognized as the standard for treating such pregnancies.